2015
DOI: 10.2166/wrd.2015.123
|View full text |Cite
|
Sign up to set email alerts
|

Prospects of desalination for irrigation water in the Sultanate of Oman

Abstract: The most limiting factor for the agricultural sector in the Sultanate of Oman is a lack of water, and security of supply in terms of both quantity and quality. Salinization of both soils and groundwater systems along the coastal strip of Al-Batinah has placed a substantial burden on farmers regarding crop selection and, therefore, farm profitability. Desalination of brackish and seawaters might be an attractive option to sustain salt-affected lands in the Sultanate, particularly given that recent advances in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
2
4
0
Order By: Relevance
“…We observed that many of the farmers dispose of the brine (EC w = 26 dS/m) directly to soil pits, old wells on their farms, or empty areas in wadies adjacent to their farms (Figure 4b). Similar occurrences of inappropriate brine disposal have also been reported by Al‐Jabri et al (2015). As more than 50% of the volume of feed water used by desalination units will be returned as brine, farmers using desalination plants produce a large volume of brine daily (Al‐Jabri et al, 2015, 2019).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…We observed that many of the farmers dispose of the brine (EC w = 26 dS/m) directly to soil pits, old wells on their farms, or empty areas in wadies adjacent to their farms (Figure 4b). Similar occurrences of inappropriate brine disposal have also been reported by Al‐Jabri et al (2015). As more than 50% of the volume of feed water used by desalination units will be returned as brine, farmers using desalination plants produce a large volume of brine daily (Al‐Jabri et al, 2015, 2019).…”
Section: Resultssupporting
confidence: 87%
“…desalination plants produce a large volume of brine daily (Al-Jabri et al, 2015. If farmers continue to inappropriately dispose of this brine, they will exacerbate the deterioration of soil and groundwater quality at a fast rate.…”
Section: Irrigation Managementmentioning
confidence: 99%
“…Figure 5 shows that only 2% of global desalinated water is used for agricultural purposes (adapted from Burn et al, 2015). Farmers in Al Batinah, and other coastal areas in Oman, are starting to use small-size desalination units to produce good-quality irrigation water for their farms (Al Jabri et al, 2015).…”
Section: World's Experience On Desalination For Agriculturementioning
confidence: 99%
“…Oman as an example Al Jabri et al (2015) explored the use of desalination in the Al Batinah coast with the following indicators (i) cost of desalination unit, (ii) operation and maintenance costs (O&M), (iii) purpose of desalination, (iv) amounts and quality of desalinated and reject brines, (v) means of disposal of brines, and (vi) types of crops grown. Table 3 summarizes cost and energy requirements of the desalination units used in the coastal farms in Al Batinah.…”
Section: Extent Of Desalination For Agriculture In Gccmentioning
confidence: 99%
“…The above discussion clearly indicates that the availability of water, in terms of quantity and quality, is the limiting factor for development and sustainability of agriculture in AlBatinah coastal strip. In efforts of sustain their agricultural practices, many farmers are currently using small, reverse-osmosis (RO) based, desalination units for irrigation water [5]. Despite the associated constraints, many countries around the world are using the desalination technology for producing irrigation water; such as Spain, Australia, Chile, USA, Italy, and several countries in the Arabia Peninsula [6].…”
Section: Introductionmentioning
confidence: 99%